2011
DOI: 10.1007/s10555-011-9324-x
|View full text |Cite
|
Sign up to set email alerts
|

Eicosanoid signalling pathways in the development and progression of colorectal cancer: novel approaches for prevention/intervention

Abstract: Arachidonic acid metabolism through cyclooxygenase (COX), lipoxygenase (LOX) and cytochrome P-450 epoxygenase (EPOX) pathways leads to the generation of biologically active eicosanoids, including prostanoids, leukotrienes, hydroxyeicosatetraenoic acid, epoxyeicosatrienoic acid and hydroperoxyeicosatetraenoic acids. Eicosanoid expression levels vary during tumor development and progression of a range of malignancies, including colorectal cancer. The actions of these autocoids are also directly influenced by die… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
46
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(47 citation statements)
references
References 193 publications
(241 reference statements)
0
46
1
Order By: Relevance
“…Recent studies have further revealed that some TCMs or their components exhibit anti-tumor activities towards several types of cancer, such as liver [12] , lung [13] , gastric [14] , nasopharyngeal [15] and colorectal cancer [16] . Non-steroidal antiinflammatory drugs have been documented in animal and human studies to reduce the risk of colorectal cancer and adenomatous polyps and have been implicated as a cancer prevention and treatment strategy [1,[17][18][19] . Longan flowers and seeds have been analyzed and were found to possess rich amounts of polyphenols, including proanthocyanidin A2, (-)-epicatechin, gallic acid and ellagic acid, and exhibit strong antioxidant and inflammatory activities [20][21][22][23][24] .…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have further revealed that some TCMs or their components exhibit anti-tumor activities towards several types of cancer, such as liver [12] , lung [13] , gastric [14] , nasopharyngeal [15] and colorectal cancer [16] . Non-steroidal antiinflammatory drugs have been documented in animal and human studies to reduce the risk of colorectal cancer and adenomatous polyps and have been implicated as a cancer prevention and treatment strategy [1,[17][18][19] . Longan flowers and seeds have been analyzed and were found to possess rich amounts of polyphenols, including proanthocyanidin A2, (-)-epicatechin, gallic acid and ellagic acid, and exhibit strong antioxidant and inflammatory activities [20][21][22][23][24] .…”
Section: Introductionmentioning
confidence: 99%
“…Human/laboratory studies [14][15][16][17][18][19][20][21][22][23][24][25][26][27][28] also suggested that n-3 PUFAs (or omega-3 PUFAs), including alpha-linolenic acid (ALA) and long-chain n-3 PUFAs (LC n-3 PUFAs) (eicosapentaenoic acid [EPA], docosapentaenoic acid [DPA], and docosahexaenoic acid [DHA]) seem to act as anti-tumor promoters in CRC carcinogenesis, like non-steroidal anti-inflammatory drugs (NSAIDs), including aspirin [29][30][31][32][33][34][35][36][37][38]. On the other hand, n-6 PUFAs (or omega-6 PUFAs, mainly linoleic acid (LA)) may act as tumor promoters, because they are upstream chemicals of n-6 family leukotrienes, thromboxanes and prostaglandins, which are catalyzed by lipoxygenase (LOX) and cyclooxygenase (COX) isoenzymes [39][40][41][42][43].…”
mentioning
confidence: 99%
“…Because a randomized controlled trial (RCT) is thought to be a high-evidence approach, we planned [46] and conducted a dietary intervention in a polypectomized participant (DIPP) study to elucidate whether n-3 PUFAs or LC n-3 PUFAs may indeed have tumor-suppressive effects. Although recent trials have provided evidence of favorable effects of n-3 PUFAs or LC n-3 PUFAs on the onset of aberrant crypt foci or CRC precursors [25][26][27], RCTs directly exploring long-term effects of n-3 PUFAs or LC n-3 PUFAs on CRTs, to the best of our knowledge, have not been conducted to date. Here, we present the results of our DIPP study.…”
mentioning
confidence: 99%
“…Arachidonic acid metabolism through cyclooxygenase, lipoxygenase, cytochrome P-450 and epoxygenase leads to overproduction of eicosanoids and plays an important role in the progress of colon neoplasia [16]. Longstanding clinical experience shows that the risk of CRC is statistically lower among people chronically using non-steroidal anti-inflammatory drugs (NSAIDs) [17,18].…”
Section: Introductionmentioning
confidence: 99%